2007
DOI: 10.2967/jnumed.107.043372
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Value of SPECT/CT in Lymphatic Mapping in Breast Cancer and Melanoma

Abstract: The recently introduced SPECT/CT integrates the physiologic data of SPECT with the anatomic data of CT into a single image. The purpose of this pilot study was to explore the additional value of SPECT/CT in breast cancer patients and melanoma patients with inconclusive planar image findings. Methods: Thirty-one patients had planar lymphoscintigrams showing unexpected lymphatic drainage, 6 had lymphoscintigrams that were difficult to interpret, and 3 showed no drainage on planar imaging. SPECT/CT was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 15 publications
(38 reference statements)
3
65
1
1
Order By: Relevance
“…Subsequent studies confirmed the value of SPECT/CT for this purpose [3,16,17,[20][21][22][23]. SPECT/CT also detected hot nodes that are not seen on conventional images.…”
Section: Spect/ct In Patients With Breast Cancersupporting
confidence: 50%
See 2 more Smart Citations
“…Subsequent studies confirmed the value of SPECT/CT for this purpose [3,16,17,[20][21][22][23]. SPECT/CT also detected hot nodes that are not seen on conventional images.…”
Section: Spect/ct In Patients With Breast Cancersupporting
confidence: 50%
“…A review of the literature on SPECT/CT for visualization and localization of sentinel nodes in patients with breast cancer revealed ten studies [3,[16][17][18][19][20][21][22][23][24]. An overview of these studies is given in Table I.…”
Section: Spect/ct In Patients With Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, SPECT/CT appears to have additional value [37] . Ploeg et al [37] limited the use of SPECT/CT to difficult and unusual cases because they believe planar lymphoscintigraphy is an excellent preoperative mapping technique for most patients. They added nonvisualization as a new indication, because SPECT/CT visualized drainage in patients whose planar images did not reveal a SLN.…”
Section: Discussionmentioning
confidence: 99%
“…Neither in the present study nor in studies of other investigators SPECT/CT did miss SLN that was visualized by planar lymphoscintigraphy [20] . Whether SPECT/CT should be used in all patients or only for specific indications needs to be studied further [37] . It is reasonable to consider utilizing SPECT/CT in conjunction with planar imaging when feasible, especially in patients with negative planar imaging, in the hope of enhancing SLN detection and localization.…”
Section: Discussionmentioning
confidence: 99%